(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Dense deployment of cellular networks is leading to scarcity of communication bandwidth or what we call as channel. If compared to its wired counterparts, wireless cellular network have limited number of channels available, which gives rise to problem of efficient channel allocation. Here, in this piece of work, the main objective is to put an effort to improve existing channel allocation scheme. In earlier existing hybrid allocation scheme, the base station notifies about the hot-spots to the Mobile Switching Centre (MSC) and if MSC has available channels in its central pool then it satisfies the request. Now, the novelty of this work starts where central pool gets exhausted and request of channels from base station (BS) still arrives and is served by returning the unused channels by different cells back to MSC on its request. The simulation of this approach is expounded and evaluated over OMNeT++ in a scenario with fixed channel allocation and hybrid approach by varying the proportion of dynamic channels to total number of channels available and the effectiveness is evaluated in terms of Call blocked and Call dropped versus System load.